Distinctive Surface Glycosylation Patterns Associated With Mouse and Human CD4+ Regulatory T Cells and Their Suppressive Function - Cabral, Joana; Hanley, Shirley A.; Gerlach, Jared Q.; O’Leary, Neil; Cunningham, Stephen; Ritter, Thomas; Ceredig, Rhodri; Joshi, Lokesh; Griffin, Matthew D. (Frontiers in Immunology, 2017)
Regulatory T-cells (T-reg) are essential for maintaining immune homeostasis and tolerance. Surface glycosylation is ubiquitous on mammalian cells and regulates diverse biological processes. While it is currently well accepted that surface glycan expression influences multiple aspects of T-cell function, little is known about the relevance of glycosylation to T reg biology. This study aimed to profile the surface glycosylation characteristics of T-reg in various lymphoid compartments of mouse and in human peripheral blood with comparison to non-regulatory, conventional CD4+ T-cells (T-conv). It also sought to determine the relationship between the surface glycosylation characteristics and suppressive potency of T-reg. Lectin-based flow cytometric profiling demonstrated that T-reg surface glycosylation differs significantly from that of T-conv in the resting state and is further modified by activation stimuli. In mouse, the surface glycosylation profiles of FoxP3+ T-reg from spleen and lymph nodes were closely comparable but greater variability was observed for T-reg in thymus, bone marrow and blood. Surface levels of tri/tetra-antennary N-glycans correlated with expression of proteins known to be involved in T-reg suppressive functions including GITR, PD-1, PD-L1, CD73, CTLA4 and ICOS. In co-culture experiments involving purified T-reg subpopulations and CD4+ or CD8+ T-conv, higher surface tri/tetra-antennary N-glycans was associated with greater T-reg suppressive potency. Enzymatic manipulation of mouse T-reg surface glycosylation resulting in a temporary reduction of surface N-glycans significantly reduced T-reg capacity to suppress T-conv activation through contact-dependent mechanisms. Overall, these findings demonstrate that T-reg have distinctive surface glycan characteristics that show variability across anatomical locations and are modulated by activation events. They also provide evidence of an important role for surface glycosylation in determining T-reg phenotype and suppressive potency. These insights may prove relevant to the analysis of T-reg in disease settings and to the further development of T-reg-based immunotherapies.